TNF-alpha regulates the effects of irradiation in the mouse bone marrow microenvironment. - Dias, Sérgio Jerónimo Rodrigues (2017)
BACKGROUND Secondary bone marrow (BM) myelodysplastic syndromes (MDS) are increasingly common, as a result of radio or chemotherapy administered to a majority of cancer patients. Patients with secondary MDS have increased BM cell apoptosis, which results in BM dysfunction (cytopenias), and an increased risk of developing fatal acute leukemias. In the present study we asked whether TNF-alpha, known to regulate cell apoptosis, could modulate the onset of secondary MDS. PRINCIPAL FINDINGS We show that TNF-alpha is induced by irradiation and regulates BM cells apoptosis in vitro and in vivo. In contrast to irradiated wild type (WT) mice, TNF-alpha deficient (TNF-alpha KO) mice or WT mice treated with a TNF-alpha-neutralizing antibody were partially protected from the apoptotic effects of irradiation. Next we established a 3-cycle irradiation protocol, in which mice were sub-lethally irradiated once monthly over a 3 month period. In this model, irradiated WT mice presented loss of microsatellite markers on BM cells, low white blood cell (WBC) counts, reduced megakaryocyte (MK) and platelet levels (thrombocytopenia) and macrocytic anemia, phenoypes that suggest the irradiation protocol resulted in BM dysfunction with clinical features of MDS. In contrast, TNF-alpha KO mice were protected from the irradiation effects: BM cell apoptosis following irradiation was significantly reduced, concomitant with sustained BM MK numbers and absence of other cytopenias. Moreover, irradiated WT mice with long term (> or = 5 months) BM dysfunction had increased BM angiogenesis, MMPs and VEGF and NFkB p65, suggestive of disease progression. CONCLUSION Taken together, our data shows that TNF-alpha induction following irradiation modulates BM cell apoptosis and is a crucial event in BM dysfunction, secondary MDS onset and progression.